Effect of roughness on particle adhesion in aqueous solutions: A study of Saccharomyces cerevisiae and a silica particle - Götzinger, Martin; Weigl, Bernhard; Peukert, Wolfgang; Sommer, Karl (Colloids and Surfaces B: Biointerfaces, 2007)
An atomic force microscope (AFM) has been used to quantify the adhesion of living cells Saccharomyces cerevisiae on three different silica surfaces with defined roughness. The effects of support roughness on the adhesion forces of a smooth silica particle were studied in addition. A living single cell was immobilized at the apex of a tipless AFM cantilever using a key-lock mechanism. Adhesion was quantified from the force-distance data measured on a smooth silica substrate and two substrates coated with hydrophilic monodisperse silica particles with 110 and 240 nm in diameter to study the effect of roughness on particle adhesion. The AFM technique gives unique insight into the primary colonization event of biofilm formation. The new knowledge helps substantially to design surface coatings relevant for biotechnology, medicine and dentistry. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: Saccharomyces cerevisiae; silica; adhesion; roughness; AFM